Ponatinib for CML patients in routine clinical practice: the PONDEROSA study - Schenk, Thomas; Fabisch, Christian; Ernst, Thomas; Ernst, Philipp; Saußele, Susanne; Žáčková, Daniela; Mayer, Jiří; Klamová, Hana; Hochhaus, Andreas (Annals of hematology, 2026)
Ponatinib, a third-generation tyrosine kinase inhibitor, is effective in patients with chronic myeloid leukemia (CML), particularly in cases of resistance or BCR::ABL1 T315I mutation. However, arterial occlusive events (AOEs) remain an important safety concern. The PONDEROSA registry evaluated ponatinib use under routine clinical conditions in Germany and the Czech Republic. This observational cohort study included 99 adult CML patients treated with ponatinib; patient recruitment took place between 2015 and 2022 at 31 centers. The median follow-up was 22 months (range: 1-83). Among the 99 patients (median age 54 years at CML diagnosis), 91.9% were in chronic phase, 4.0% in accelerated phase, and 4.0% in blast phase. The T315I BCR::ABL1 mutation was detected in 19.2%. Ponatinib starting doses were 45 mg/day (32.3%), 30 mg/day (37.3%), or 15 mg/day (29.3%). Adverse events (AEs) were recorded in 64.6% of patients. Severe cardiovascular or cerebrovascular events occurred in 12.1% of patients, with no fatal events observed. Ponatinib was discontinued in 31.3% of patients, mainly due to intolerance or lack of response. 58.6% of patients achieved or maintained at least a major molecular response (MMR), compared to 19.0% at baseline. Disease progression was observed in 14.1% of patients, and 8.1% underwent allogeneic stem cell transplantation. The estimated 2-year progression-free survival and overall survival rates were 84.4% and 85.7%, respectively. The PONDEROSA study confirms the clinical effectiveness of ponatinib in routine practice. Individualized dosing strategies are essential to balance efficacy and cardiovascular safety. Ponatinib remains a valuable bridging therapy for patients requiring allogeneic transplantation.
Gesehen am 12.02.2026